Land Evaluation for Oil Palm Plantation on Peat Soil in Pondok Kelapa District, Midle Bengkulu Regency of Bengkulu Province - Alex Chandra Situmeang; Kanang Setyo Hindarto; Prasetyo Prasetyo (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2019)
The development of oil palm plantations in Indonesia as a commodity crop has increased rapidly from year to year. The oil palm plant in Pondok Kelapa District, Middle Bengkulu Regency is the second-largest plantation of people after oil palm. Increasing the income and welfare of farmers can also be done through the evaluation of peatland custom in oil palm crops. This study aims to evaluate the suitability and analyze peatland limiting factors for oil palm plants in Pondok Kelapa District and provide peatland processing direction based on limiting factors to produce palm oil production in Pondok Kelapa District. This research was conducted in Pondok Kelapa Bengkulu Tengah Regency from December 2014 until January 2015 through 4 stages, namely pre-survey, field survey, data analysis, and making a map of the potential development of oil palm plantations. The results showed that each observation point has a low to moderate soil fertility rate It is characterized by low pH and N total values, as well as low P2O5 in providing nutrients for oil palm plants. In general, limiting factors are the dominant limiting factors, namely available nutrients (P2O5, N total) and nutrient retention (pH). The results of land suitability evaluation in Pondok Kelapa District showed the land suitability class is S2 and S3, actual land suitability class for oil palm plants in Pondok Kelapa District with barrier factors hampered drainage, fertility/low soil nutrients, and soil drainage is very hampered/very bad. Efforts to increase peatland potential for oil palm crops can be done by improving drainage, planting systems, and high maintenance of groundwater levels in oil palm plants.